2008
DOI: 10.1158/0008-5472.can-07-3218
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Recurrent Chromosomal Inversion Implicates the Homeobox GeneDlx5in T-Cell Lymphomas from Lck-Akt2 Transgenic Mice

Abstract: The oncogene v-akt was isolated from a retrovirus that induced murine thymic lymphomas. Transgenic mice expressing a constitutively activated form of the cellular homologue Akt2 specifically in immature T cells develop spontaneous thymic lymphomas. We hypothesized that tumors from these mice might exhibit oncogenic chromosomal rearrangements that cooperate with activated Akt2 in lymphomagenesis. Cytogenetic analysis revealed a recurrent clonal inversion of chromosome 6, inv(6), in thymic lymphomas from multipl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 18 publications
0
63
0
Order By: Relevance
“…The rag2:myr-mAkt2 construct was generated by placing a myristoylated murine Akt2 transgene (19), which is constitutively activated as a result of constitutive membrane localization, downstream of a zebrafish rag2 promoter fragment (25) in a modified pBluescript vector, wherein the rag2:myr-mAkt2 construct is flanked by recognition sequences for I-SceI meganuclease.…”
Section: Methodsmentioning
confidence: 99%
“…The rag2:myr-mAkt2 construct was generated by placing a myristoylated murine Akt2 transgene (19), which is constitutively activated as a result of constitutive membrane localization, downstream of a zebrafish rag2 promoter fragment (25) in a modified pBluescript vector, wherein the rag2:myr-mAkt2 construct is flanked by recognition sequences for I-SceI meganuclease.…”
Section: Methodsmentioning
confidence: 99%
“…2 In some Lck-Myr-Akt2 founder lines, a recurrent chromosomal inversion implicated the homeobox gene Dlx5 as an oncogene. 3 In subsequent work (manuscript in preparation), we found that transgenic Lck-Dlx5 mice develop spontaneous thymic lymphomas that acquire constitutive activation of Akt, due to loss of Pten expression, as well as up regulation of Myc. Such genetic and epigenetic changes are characteristics of other acute T-cell lymphoma animal models as well as human T-ALLs.…”
Section: Discussionmentioning
confidence: 89%
“…2 Tumors from these transgenic mice consistently harbor one or the other of 2 recurrent chromosomal rearrangements that each involve somatic juxtaposition of a T cell receptor (TCR) enhancer and a transcription factor gene, either Dlx5 or Myc -in each case resulting in unregulated expression of Myc protein. 3 Myc is thought to be essential to T cell development, and Myc-null T cells fail to proliferate at the CD4/CD8 double-negative stage in mice. 4 While overexpression of Myc drives T-ALL in zebrafish, transgenic mice specifically overexpressing Myc in immature T cells, under the control of an Lck promoter, did not develop T-ALL, indicating that Myc is necessary, but not sufficient, to induce T-cell malignancy in mice.…”
Section: Introductionmentioning
confidence: 99%
“…27 In addition, a recent study has found that a gene crucial for embryonic development can quickly become a potent cancer promoter in adult mice following a genetic misalignment, indicating that embryonic genes can become cancer inducers. 47 Although Oct-4 is normally expressed in embryonic stem cells and germ cells, and it is required for maintaining their pluripotency, it can also promote tumorigenesis when expressed inappropriately. 22,23,27,29 In addition, Oct-4 is expressed in human tumors, including testicular germ cell tumor and breast carcinoma, and it plays a part in human cancer development.…”
Section: Discussionmentioning
confidence: 99%